Interest in using electronic money: The effect of perceived ease of use, perceived usefulness, security, service features, and attitude of use - Iis Naini; Rahmiati (Universitas Negeri Padang, 2022)
This study aims to determine the effect of ease of use, usefulness of using technology, security, and service features on Interest to use electronic money, with usage attitude as an intervening variable. This study uses quantitative research methods. This research was conducted in the city of Padang. The population in this study were all electronic money users in the city of Padang. Determination of the sample in this study, using a non-probability sampling sample selection method. The sample that will be used as respondents from this research is as many as 580 people of Padang City who use electronic money. The results of this study indicate that ease of use has a positive and significant effect on interest to use, usefulness of using has a positive and significant effect on interest to use, safety of use has a positive but not significant effect on interest to use, service features use a positive but not significant effect on interest to use, ease of use has a positive and significant effect on attitudes to use, usefulness of use have a positive and significant effect on attitudes of use, safety of use has a positive and significant effect on attitudes of use, service features of use have a positive and significant effect on attitudes of use, attitudes of use have a positive and significant effect on interest to use.